Association of Asymmetrical Dimethyl Arginine with Diabetes Mellitus and Coronary Artery Disease - Tariq, Kalsoom (International Journal of Pathology, 2023)
Background: The individuals with Diabetes Mellitus (DM) have a large incidence of coronary artery diseases.Objective: To compare the association of serum Asymmetrical dimethyl arginine (ADMA) level in diabetic patients with and without coronary artery disease. Serum ADMA acts as an endogenous nitric oxide synthase (NOS) inhibitor by competing with arginine for the active site. It is increased in the plasma of humans in different abnormal conditions like cardiac diseases, diabetes, atherosclerosis, hypercholesterolemia, hypertension and chronic renal failureMethods: This analytical cross sectional study was conducted in the medical departments of Khyber teaching hospital & Hayatabad medical complex from October 2010 to October 2011. Both males & females’ patients of age range of 35-65 years were included in the study. Of 210 participants 70 were included in three groups, A: normal participants, B: Type 2diabetic patients & C: diabetic patients with coronary artery diasease(CAD). Biochemical analysis was done on blood sample of these participants for ADMA, lipid profile, HbA1C & fasting blood sugar.Results: ADMA was found to be raised in both the diabetics groups with & without CAD as compared to the normal participants (03.9±1.5μmol/L vs. 02.0±0.6 and 0.6±0.2 μmol/L) p <0.0001. Amongst the diabetic groups ADMA was higher in the diabetics with CAD as compared to diabetics without CAD. Similarly lipid profile values of LDL, Total cholesterol, triglycerides were higher in the two groups of diabetics with & without CAD as compared to the normal individuals.Conclusion: The diabetic patients with coronary artery disease had significantly higher serum ADMA concentration than simple diabetics and normal healthy subjects.